An Experimental Study On Flow Field Around Inundate Bell Mouth Groin - Uddin, MJ; Hossain, MM; Hossain, SAA Mamun (Kathmandu University Journal of Science, Engineering and Technology, 2012)
A study was undertaken to investigate the flow field around bell mouth groin in a large mobile bed physical model facility (46m x 11 m). A total number of 24 test runs were conducted. Three different discharges and four different angles and two groin conditions (submerged and non-submerged) was considered. All tests were conducted for 8 hours duration in clear water condition. Velocity data have been collected forming grids in both vertical and horizontal direction around the vicinity of the bell mouth groin. Velocity was measured at 0.2, 0.4, 0.6 and 0.8 depths from the water surface by forming grids. Change in flow conditions around bell mouth groin for various test run have been analyzed non-dimensionally in longitudinal, lateral and vertical direction. The streamwise velocity along lateral direction was found that the lateral shifting of maximum velocity away from the head of the bell mouth groin. In most cases, streamwise vertical velocity in lower part of the channel is found higher than that of upper part. Streamwise vertical velocity profile has been found variable with different discharges and does not follow its natural logarithmic pattern. Velocity vector indicates that flow is steady at upstream along longitudinal direction. The flow diverted at head of structure and flows through sides of structure towards downstream. A circulation of flow has been observed around head of structure after diverting of flow towards down. Immediately after rear front of structure, relatively weak circulation of flow has been observed. In this paper the results of test runs conducted under submerged conditions for 1500 and 900 angles are reported. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6050 KUSET 2012; 8(1): 104-118